University leadership as engaged pedagogy: A call for governance reform - Ryan, Juliana; Goldingay, Sophie (Journal of University Teaching and Learning Practice, 2022)
Responses to COVID-19 impacts have shown how quickly universities can change, given the impetus. However, global disruptions to university learning and teaching have not yet been matched by any significant change to university leadership. Taking gender equity as our focus, we argue that pedagogical disruption should extend beyond the classroom to reshape academic leadership. In this commentary we critically reflect on the question ‘How can university leaders share power to nurture caring and ethical academic leadership’? Taking some cues from disruptions to university learning and teaching, we call on the work of bell hooks to propose a holistic vision of university leadership as a form of critical pedagogy — ‘engaged pedagogy’. We draw on combined experience in professional and academic roles at six universities in Australia and Aotearoa New Zealand to share composite vignettes of holistic leadership practices grounded in integrity, collaboration and personal wellbeing. Our commentary concludes with practical suggestions for changing university governance in a time of disruption so that leadership as engaged pedagogy can be practised more widely.